Human cancer-targeted immunity via transgenic hematopoietic stem cell progeny - Theodore S. Nowicki; Nataly Naser Al Deen; Cole W. Peters; Begoña Comin-Anduix; Egmidio Medina; Cristina Puig-Saus; Ignacio Baselga Carretero; Paula Kaplan-Lefko; Mignonette H. Macabali; Ivan Perez Garcilazo; Daniel Chen; Jia Pang; et al. (Nature Communications)
Abstract Adoptive transfer of genetically engineered T cells expressing a tumor-antigen-specific transgenic T cell receptor (TCR) can result in clinical responses in a variety of malignancies. However, these responses are frequently short-lived, and patients typically relapse within several months. This phenomenon is largely due to poor persistence of the transgenic T cells, as well as a progressive loss of their functionality and terminal differentiation in vivo. This underscores the need for cell therapy approaches able to sustain the initial antitumor efficacy and lead to long-term antitumor efficacy. Herein, we report the use of tandem cell therapies involving autologous T cells and hematopoietic stem cells engineered to express the NY-ESO-1 TCR for the treatment of solid tumors in a first-in-human phase I clinical trial (NCT03240861). This therapy is shown to be safe, feasible, and leads to initial tumor regression activity. T cell progeny from the HSC progenitors is shown to provide circulating transgenic NY-ESO-1 TCR-T cells, which display tumor-antigen-specific antitumor functionality, without any evidence of anergy or exhaustion. These results demonstrate the utility of transgenic HSCs to generate a self-renewing source of tumor-specific cellular immunotherapy in human participants. Clinicaltrials.gov: NCT NCT03240861